Minimality and identifiability of discrete‐time switched autoregressive exogenous systems. (16th July 2020) - Petreczky, M.; Bako, L.; Lecoeuche, S.; Motchon, K. M. D.
Summary: This article studies the problem of minimality and identifiability for switched autoregressive exogenous (SARX) systems. We propose formal definitions of the concepts of identifiability and minimality for SARX models. Based on these formalizations, we derive conditions for minimality and identifiability of SARX systems. In particular, we show that polynomially parameterized SARX systems are generically identifiable.